2019
DOI: 10.1103/physrevb.99.235116
|View full text |Cite
|
Sign up to set email alerts
|

Optical signature of the pressure-induced dimerization in the honeycomb iridate αLi2IrO3

Abstract: We studied the effect of external pressure on the electrodynamic properties of α-Li2IrO3 single crystals in the frequency range of the phonon modes and the Ir d-d transitions. The abrupt hardening of several phonon modes under pressure supports the onset of the dimerized phase at the critical pressure P c=3.8 GPa. With increasing pressure an overall decrease in spectral weight of the Ir d-d transitions is found up to P c. Above P c, the local (on-site) d-d excitations gain spectral weight with increasing press… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…This value of p c | T =0 corresponds to zero temperature, as no thermal effects have been taken into account. Such a critical pressure is much lower than 3.8 GPa expected from the previous roomtemperature measurements [14,19,22], yet it nearly coincides with the low-temperature value of p c inferred from our magnetization data (Fig. 4).…”
Section: Ab Initio Modeling Thermodynamic Stabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…This value of p c | T =0 corresponds to zero temperature, as no thermal effects have been taken into account. Such a critical pressure is much lower than 3.8 GPa expected from the previous roomtemperature measurements [14,19,22], yet it nearly coincides with the low-temperature value of p c inferred from our magnetization data (Fig. 4).…”
Section: Ab Initio Modeling Thermodynamic Stabilitysupporting
confidence: 90%
“…Hydrostatic pressure is a cleaner tuning parameter that does not introduce randomness but potentially drives structural phase transitions that necessarily affect magnetism. In this context, x-ray diffraction (XRD) [19][20][21], optical spectroscopy [22], and Raman spectroscopy [14] on α-Li 2 IrO 3 defined p c ≃ 3.8 GPa as the critical pressure of the structural phase transition at room temperature. Above p c , α-Li 2 IrO 3 changes its symmetry from monoclinic to triclinic [19] and becomes non-magnetic owing to the formation of short Ir-Ir bonds (dimerization).…”
Section: Introductionmentioning
confidence: 99%
“…External pressure was considered as a convenient tuning parameter that may reduce the unwanted interactions, suppress magnetic order, and bring a material closer to the Kitaev limit [4,5]. However, hydrostatic pressure experiments performed on several model compounds -different polymorphs of Li 2 IrO 3 [6] and α-RuCl 3 [7][8][9][10] -all revealed a competing structural instability (dimerization) that shortens one third of the metal-metal distances on the (hyper)honeycomb spin lattice and eliminates local magnetism of the 4d/5d ions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, both external pressure and chemical methods such as hydrogen intercalation have been used to modify the lattice structure of various Kitaev materials. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] In particular, a recent high-pressure study of β-Li 2 IrO 3 with x-ray diffraction found a signature of a structural transition from the orthorhombic structure at ambient pressure (F ddd space group, No. 70, mmm point group) 9,19 to a lower-symmetry monoclinic structure (C2/c space group, No.…”
Section: Introductionmentioning
confidence: 99%